A case report on severe nivolumab-induced adverse events similar to primary sclerosing cholangitis refractory to immunosuppressive therapy. Issue 23 (11th June 2021) - Hirasawa, Yuya; Yoshimura, Kiyoshi; Matsui, Hiroto; Kubota, Yutaro; Ishida, Hiroo; Arai, Jun; Sakaki, Masashi; Oguro, Nao; Shida, Midori; Taniguchi, Makoto; Hamada, Kazuyuki; Ariizumi, Hirotsugu; et al.
Abstract: Introduction: Immune checkpoint inhibitors (ICIs), particularly anti-PD-1 antibody, have dramatically changed cancer treatment; however, fatal immune-related adverse events (irAEs) can develop. Here, we describe a severe case of sclerosing cholangitis-like irAE. We report the use of 3 immunosuppressive agents that resulted in the death of the patient due to treatment inefficacy. According to a postmarketing study of nivolumab, the frequency of ICI-related sclerosing cholangitis is 0.27% and that of ICI-related cholangitis is 0.20%. There have been 4 case reports of sclerosing cholangitis-like irAE, with imaging findings, including typical intrahepatic bile duct beaded constriction in primary sclerosing cholangitis. Treatment starts with prednisolone and is combined with an immunosuppressant in refractory cases. There are no reports of severe cases that ultimately led to death. Patients concerns: The patient is a 64-year-old male with Stage IV squamous cell lung carcinoma; he was hospitalized with abdominal pain and elevation of aspartate transaminase and alanine transaminase, approximately 4 months after ICI administration was suspended. This occurred because the patient treated with nivolumab as the second-line chemotherapy and developed type 1 diabetes mellitus after 11 courses. Diagnosis: A grade 3 increase in bilirubin was observed and he was diagnosed with sclerosing cholangitis, based on magnetic resonance cholangiopancreatography imaging and pathological findings of the liver and bile duct. Interventions: Prednisolone, mycophenolate mofetil, and tacrolimus combination therapy was administered. Outcomes: The treatment was difficult and failed. He died from liver failure 8 months after diagnosis. In this case, hepatitis and cholangitis, mainly alanine transaminase-dominant liver disorder, developed in the early stages of irAEs. Although he showed some improvement after prednisolone administration, bilirubin levels began rising again, and sclerosing cholangitis did not improve even with the use of 3 immunosuppressive agents recommended by the ESMO Clinical Practice Guidelines for immune-related hepatotoxicity management. Although the antitumor effect showed a complete response, liver failure led to death. Conclusion: This is the first case report on the ineffectiveness of triple immunosuppressant combination therapy recommended by the guidelines for immune-related hepatotoxicity. It is necessary to develop more appropriate treatment for severe sclerosing cholangitis-like irAE based on the robust evidence.